PHYSICAL PROPERTIES OF THE LEAD SELENIDE AND THEIR TRANSFORMATION AFTER IR LASER EMISSION TREATMENT - Kadyshev, S.K. (Recent Contributions to Physics, 2018)
Electrical and optical properties and electron spin resonance of the undoped and doped lead selenide before and after IR laser emission treatment in the matrix transparency region have been studied.